2015
DOI: 10.1016/j.neuroimage.2014.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Decreased auditory GABA+ concentrations in presbycusis demonstrated by edited magnetic resonance spectroscopy

Abstract: Gamma-aminobutyric acid (GABA) is the main inhibitory neurotransmitter in the central auditory system. Altered GABAergic neurotransmission has been found in both the inferior colliculus and the auditory cortex in animal models of presbycusis. Edited magnetic resonance spectroscopy (MRS), using the MEGA-PRESS sequence, is the most widely used technique for detecting GABA in the human brain. However, to date there has been a paucity of studies exploring changes to the GABA concentrations in the auditory region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 53 publications
4
47
0
1
Order By: Relevance
“…One of the most consistent changes within the central auditory system following hearing loss and accompanying ageing is the reduction in neural inhibition along the ascending auditory pathway (Raza et al ., ; Caspary et al ., , ; Vale et al ., ; Burianova et al ., ; Takesian et al ., , ; Llano et al ., ; Rabang et al ., ; Gao et al ., ). Accordingly, recent observations of enhanced neural responses (excitability) due to hearing loss and ageing have been discussed in the context of reduced neural inhibition (Hughes et al ., ; Herrmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…One of the most consistent changes within the central auditory system following hearing loss and accompanying ageing is the reduction in neural inhibition along the ascending auditory pathway (Raza et al ., ; Caspary et al ., , ; Vale et al ., ; Burianova et al ., ; Takesian et al ., , ; Llano et al ., ; Rabang et al ., ; Gao et al ., ). Accordingly, recent observations of enhanced neural responses (excitability) due to hearing loss and ageing have been discussed in the context of reduced neural inhibition (Hughes et al ., ; Herrmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we aimed to investigate this correlation in the auditory cortex. It is only recently that MRS studies were capable of measuring GABA or glutamate concentrations in the auditory cortex [Gao et al, ; Hugdahl et al, ; Kompus et al, ]. Limitations in the choice of placement of the MRS voxel were due to the fact that better signal‐to‐noise ratios were achieved in brain regions such as the occipital cortex in close proximity to the MR coil elements [Puts and Edden, ].…”
Section: Discussionmentioning
confidence: 99%
“…State‐of‐the‐art MRS‐based GABA measurement methods do not allow satisfying signal‐to‐noise ratios in measuring the tiny spectrum within small volumes, for example, primary auditory cortex [Puts and Edden, ]. Compared to other studies required even larger volumes (4 × 3 × 3 cm 3 ) using the MEGA‐PRESS sequence in auditory cortex [Gao et al, ], we managed to reduce voxel size with optimized parameters. Studies of morphology in primary auditory cortex state that the sizes vary in individuals between 0.5 and 3 cm 3 [Penhune et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…One MR spectroscopy study demonstrated that gamma-aminobutyric acid concentrations were reduced in the auditory cortex of patients with presbycusis. 31 The inhibition-deficit hypothesis is also considered the reason for the decline in several other cognitive domains, such as reading. 32 Altered DTI parameters were also found near the insula in patients with presbycusis.…”
Section: Discussionmentioning
confidence: 99%